2013
DOI: 10.1177/0731684413503720
|View full text |Cite
|
Sign up to set email alerts
|

Moisture absorption and mechanical degradation studies of polyurethane foam cored E-glass-reinforced vinyl-ester sandwich composites

Abstract: The present paper explores the experimental observations and result of hygrothermic aging of polyurethane foam cored E-glass reinforced vinyl-ester sandwich composites for a long duration of time under salt fog exposure. Four types of sandwich specimens were used for the study. Polyurethane foam cored E-glass mat (woven roving, chopped strand mat, chopped strand stitched mat and stitch bond mat) type reinforcement in vinyl-ester sandwich composites were prepared by manual hand layup method using compression te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…A similar finding has also been discussed by Li and Weitsman . Several other studies also observed that the polymeric foam core degrades after a long‐time exposure to fluid, see for example Avilés and Aguilar‐Montero and Manujesh et al . Morganti et al studied the effects of moisture on sandwich composites and reported that fluid diffusion degraded the matrix elastic properties and induced microcracks between fibers and matrix.…”
Section: Introductionsupporting
confidence: 71%
“…A similar finding has also been discussed by Li and Weitsman . Several other studies also observed that the polymeric foam core degrades after a long‐time exposure to fluid, see for example Avilés and Aguilar‐Montero and Manujesh et al . Morganti et al studied the effects of moisture on sandwich composites and reported that fluid diffusion degraded the matrix elastic properties and induced microcracks between fibers and matrix.…”
Section: Introductionsupporting
confidence: 71%
“…Apart from the mechanical behavior of PUF sandwiches, some researchers in past years have studied their response in other areas such as moisture absorption, insulating behavior and damping response etc. Manujesh et al studied the effects of moisture absorption on the mechanical behavior of PUF sandwich composites. Four different types of sandwich specimens were manufactured using woven roving (WR), chopped strand mat (CSM), stitched bond mat (SBM) and chopped strand stitched mat (CSM‐S) fabrics for face sheets.…”
Section: Puf Core Sandwich Structuresmentioning
confidence: 99%
“…A, Specimen with PUF core density of 100 kg/m 3 . B, Specimen with PUF core density of 300 kg/m 3 [Color figure can be viewed at wileyonlinelibrary.com]…”
Section: Puf Core Sandwich Structuresmentioning
confidence: 99%
“…Additional studies [11][12][13] have also indicated that polymer foams' mechanical properties are substantially affected by moisture absorption. Several researchers [14][15][16] investigated the mechanical degradation of foam-cored sandwich structures exposed to varying hygrothermal conditions.…”
Section: Introductionmentioning
confidence: 99%